How Corporate Social Responsibility Can Effect on the Consumers’ Attitude and Behavior?: A Conceptual Study - Qasim, Saba; Siam , Mohammad R.A; Sallaeh, Salniza Bt Md (Asian Journal of Empirical Research, 2017)
Corporate Social Responsibility (CSR) is a marketing tool that significantly affects the consumers’ attitude and behavior. The study investigates the positive and negative effects of CSR, consumers’ attitude and behavior. Furthermore, examine trust as a mediator between CSR and consumers’ attitude and CSR and consumers’ behavior also the part of this study. This paper provides companies to understanding regarding the consumers’ attitude and behavior about CSR. This study conclude that CSR may be associated with an overall higher performance in positively influence the consumers’ attitude and behavior. The CSR is being considered as a showcasing methodology, which adds to the information of administrators and gives more extensive advantages to their organizations by improving an image and building a corporate brand value. The directions in understanding the effect of CSR in fortifying the association with consumers.